Scaling up a monitoring and evaluation framework for sexual, reproductive, maternal, newborn, child, and adolescent health services and outcomes in humanitarian settings: A global initiative - Loulou Kobeissi; Thidar Pyone; Allisyn C. Moran; Kathleen L. Strong; Lale Say (Elsevier, 2022)
Background: Reliable and rigorously collected sexual, reproductive, maternal, newborn, child, and adolescent (SRMNCAH) data from humanitarian settings are often sparse and variable in quality across different settings due to the lack of a standardised set of indicators across the different agencies working in humanitarian settings. This paper aims to summarise a WHO-led global initiative to develop and scale up an SRMNCAH monitoring and evaluation framework for humanitarian settings. Methods: This research revolved around three phases. The first and the last phase involved global consultations with lead international agencies active in SRMNCAH in humanitarian settings. The second phase tested the feasibility of the proposed indicators in Afghanistan, Bangladesh, the Democratic Republic of the Congo, and Jordan, using different qualitative research methods (interviews with 92 key informants, 26 focus group discussions with 142 key stakeholders, facility assessments and observations at 25 health facilities or sites). Results: Among the 73 proposed indicators, 47 were selected as core indicators and 26 as additional indicators. Generally, there were no major issues in collecting the proposed indicators, except for those indicators that relied on death reviews or population-level data. Service availability and morbidity indicators were encouraged. Abortion and SGBV indicators were challenging to collect due to political and sociocultural reasons. The HIV and PMTCT indicators were considered as core indicators, despite potential sensitivity in some settings. Existing data collection and reporting systems across the four assessed humanitarian settings were generally fragmented and inconsistent, mainly attributed to the lack of coordination among different agencies. Interpretation: Implementing agencies need to collaborate effectively to scale up this agreed-upon set of SRMNCAH framework to enhance accountability and transparency in humanitarian settings.